Forensic Analysis of Salivary Nicotine by Calix[4]Arene Customized Gold Nanoparticles in Water and Soil - Goswami, Heena; Mathew, Thomas (International Journal of Membrane Science and Technology, 2023)
Nicotine, a potent stimulant found in tobacco products, has significant effects on oral health and overall well-being. Saliva samples showing the presence of nicotine can be very helpful as evidence in a variety of situations. Salivary nicotine levels can reveal smoking habits. It offers proof of whether a person has recently used tobacco goods. Saliva testing can be used, for instance, to support or contradict smoking behaviours in court cases involving custody disputes, child endangerment, or employment regulations. Saliva nicotine testing can be used in criminal investigations to determine a suspect’s smoking history. If saliva includes nicotine traces, it can be used to identify the person to a place or occasion, particularly at the crime scene which may reveal discarded cigarette butts or other tobacco-related evidence. Also, exposure to nicotine impacts general health. Saliva tests can reveal whether or not a person uses tobacco, which is important information for determining health risks. For example, nicotine testing can be used by medical practitioners to assess a patient’s willingness to stop smoking or to track their progress while participating in smoking cessation programmes. Moreover, some insurance providers take nicotine usage into account when setting insurance premiums or providing coverage. Saliva test results can impact judgments about disability claims, health insurance, and life insurance. However, it’s crucial to properly interpret the findings of nicotine tests. Due to the variety of benefits associated with the identification of salivary nicotine, this article aims to develop an affordable technique that can facilitate the in-situ, real-time detection of nicotine in saliva samples.